2012
DOI: 10.1016/s2255-4971(15)30033-1
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous Anterior Transposition for Treatment of Cubital Tunnel Syndrome: Is This Method Safe and Effective?

Abstract: Objective: To evaluate the results from subcutaneous anterior transposition of the cubital nerve for treating cubital tunnel syndrome (CTS) and the influence of prognostic factors such as preoperative McGowan stage, age and duration of symptoms. Methods: 36 patients with CTS who underwent subcutaneous anterior transposition of the cubital nerve between 2006 and 2009 were evaluated after an average follow-up of 28 months. Their mean age was 41.6 years. Nine patients were in McGowan stage I, 18 in stage II and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Of these, 78% of patients presented severe neuropathy and improved after surgery, with a satisfaction rate of 86%, and with 72% returning to daily activities without limitations. 3 In Asia, a study conducted in Korea from 2010 to 2012, with 69 patients submitted to ulnar nerve transposition surgery, showed that their mean age was 36 years-old and there was a male prevalence (59%). 13 In the United States, a study with 25 patients (14 men and 11 women) undergoing surgery between 2003 and 2009 observed that their mean age was 53 years-old.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 78% of patients presented severe neuropathy and improved after surgery, with a satisfaction rate of 86%, and with 72% returning to daily activities without limitations. 3 In Asia, a study conducted in Korea from 2010 to 2012, with 69 patients submitted to ulnar nerve transposition surgery, showed that their mean age was 36 years-old and there was a male prevalence (59%). 13 In the United States, a study with 25 patients (14 men and 11 women) undergoing surgery between 2003 and 2009 observed that their mean age was 53 years-old.…”
Section: Discussionmentioning
confidence: 99%
“…These etiologies include metabolic alterations, congenital abnormalities, elbow trauma sequelae, tumors, osteoarthrosis and nerve subluxation in the medial epicondyle during elbow flexion. 3 Epidemiological data show that its worldwide incidence is estimated at 25 cases per 100,000 people/year, with men being affected twice more than women, and with the highest impairment between the fourth and fifth decades of life. 1,2 Italy presents the same worldwide incidence: 25 cases per 100,000 people/year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Thin patients are prone to repeated minor traumas after AST. 12 Osterman et al 13 pointed out that if AST fails, submuscular transposition is used to provide an unscarred bed for the ulnar nerve. In spite of numerous comparative retrospective reports of these procedures, no comparison between AST and AIT has been made.…”
Section: Discussionmentioning
confidence: 99%
“…Этот же способ используют также при лечении рецидивирующего вывиха-подвывиха локтевого нерва и для устранения значительного диастаза при сшивании поврежденного локтевого нерва. С целью предупреждения вывихивания после передней подкожной транспозиции локтевой нерв фиксируют в перемещенном положении адипозными, фасциальными лоскутами-блоками [3,7,9]. Мы разработали и используем способ фиксации перемещенного нерва [8].…”
Section: Discussionunclassified